3D Highly Conductive Silver Nanowire@PEDOT:PSS Composite Sponges for Flexible Conductors and Their All‐Solid‐State Supercapacitor Applications. Issue 22 (18th September 2017) - Moon, In Kyu; Yoon, Seonno; Oh, Jungwoo
Abstract: Although increasing attention has been paid to wearable electronic devices in recent years, flexible supercapacitors with high performance remain not readily available because of the limitations of flexible electrode types. A highly conductive 3D macroporous sponge is fabricated by coating poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)/silver nanowires (AgNWs) on a commercial sponge using a simple and low‐cost "immersion method." The fabricated flexible 3D sponge conductor shows a high electrical conductivity of 3.94 × 10 −4 S cm −1 with good stability in various environments and under bending deformation. To exploit the potential of the flexible 3D PEDOT:PSS/AgNW coating on the sponge as a current collector for energy‐related applications, urchin‐like Co(OH)F arrays are directly grown on PEDOT:PSS/AgNW‐on‐sponge conductors for all‐solid‐state supercapacitors. The resulting symmetric all‐solid‐state supercapacitor exhibits a mass‐specific capacitance of 103.7 F g −1 at a current density of 1 A g −1, retaining 85.8% of the initial capacitance after 3000 cycles, and mechanical flexibility during bending. This fabrication of the 3D lightweight conductor can be easily scaled up for mass production and introduces new opportunities for flexible electronic applications. Abstract : A new Co(OH)F nanowire array electrode on a flexible polyurethane sponge (PUS)/Ag nanowire (AgNW)/poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) conductor has been developed by combining hydrothermal growth with a wet‐coating‐processing material. This PUS/AgNW/PEDOT:PSS conductor is highly conductive and chemically stable. The all‐solid‐state Co(OH)F supercapacitor offers a new high‐performance supercapacitor electrode design with significantly improved specific capacitance.